Ibrutinib as an antitumor immunomodulator in patients with refractory chronic lymphocytic leukemia. (1st December 2016) - Cubillos-Zapata, Carolina; Avendaño-Ortiz, Jose; Córdoba, Raúl; Hernández-Jiménez, Enrique; Toledano, Victor; Pérez de Diego, Rebeca; López-Collazo, Eduardo
ABSTRACT: Ibrutinib has emerged as a promising therapy for patients with chronic lymphocytic leukemia (CLL) who are nonresponsive to standard therapies. The refractory state of monocytes and T-cell exhaustion in patients with CLL could explain the morbidity and mortality reported in these patients. We studied the effect of ibrutinib on the immune response of four relapsed patients with CLL during the first treatment cycle. We observed the ability to recover the standard response against bacterial stimulus in CD14 + cells, improving levels of phospho-Erk1/2 and antigen presentation. Meanwhile, ibrutinib drove Th1-selective pressure in T lymphocytes, thus, reducing the PD-1 and PDL-1 expression. Our data suggest the impact of BTK inhibition along with immunomodulation on the innate immune response and a switch to the specific adaptive immune response, which might help to decrease infectious complications. The potential effect of ibrutinib on CLL patient outcomes is worthy of further study, because infections could be reduced with the use of ibrutinib.